Rebellion of Lubomirski and its influence on making political system reforms in 17th and 18th c. in Poland - Hnatów, Anna (Видавництво Львівської політехніки, 2011)
An article presents Lubomirski’s rebellion and its influence on political reforms in Poland in 17th and 18th c. In 17th c. Polish king Jan Kazimierz perceived main faults of political system in Poland and tried to reform the constitution bymaking attemps to strengthen political position of monarch using changes rules of election of king. Due to the conflict with Jerzy Lubomirski, which turned into rebellion, king had to resign from his plans of reforms. Rebellion of Lubomirski caused negative consequences for Poland because from this time Polish nobility regarded king’s projects of reforms with suspicion and opposed to every attempts to strengthen monarch’s political position. It was a main reason why political reforms in Poland in 17th and 18th c. didn’t end successful.
Бунт Любомирського і його вплив на створення реформ політичної системи в Польщі XVII–XVIII cт.
Keywords: conflict between king and the great marshal; internal situation in Poland; political system; political system faults; projects of reformes